Optimization of photochromic Br-hackmanite materials for optical film and eyewear applications - Muurinen, Bettiina (My University, 2024)
Hackmanite (Na8(Al6Si6O24)(Cl,S)2), a sulfur-doped sodalite mineral, exhibits reversible photochromism, meaning it changes color under UV light and fades back to its initial color when exposed to visible light or heat. This unique property makes hackmanite a promising candidate for applications in photochromic eyewear, optical coatings, and UV sensors. As the amount of harmful UV radiation reaching the Earth’s surface has significantly increased in recent years, there is a growing need for effective UV protection and monitoring tools. Photochromic sensors that change color under UV light provide a rapid, visual indication of excessive UV exposure. Similarly, photochromic eyewear darkens in sunlight, functioning like sunglasses to protect the eyes and the sensitive surrounding skin from harmful radiation. In this work, the primary goal was to determine optimal synthesis conditions for hackmanite, enhance its photochromic response, and evaluate its suitability for photochromic films and potential eyewear applications. Bromide was substituted for chloride in the hackmanite structure, and various parameters, including annealing and reduction temperatures, grinding duration, and boron addition, were investigated to enhance the material’s photochromic properties. Hackmanite films were fabricated with attention to mass percentage optimization, thickness consistency, and aggregation control through surfactants. The results showed that higher color intensity resulted in more opaque material, and that attempts to enhance transmittance through aggregation control or reducing the crystallite size were ineffective. These limitations suggest that there are significant challenges hindering the development of a transparent hackmanite lens material suitable for commercial use, and further research needs to be done. However, while hackmanite may not be ideal for transparent applications like eyewear, it holds significant potential for UV sensors and similar applications where transparency is not a critical requirement.
Keywords: hackmanite, photochromic eyewear, UV sensoring, photochromism